4(ax+3)-ax=25+3a

Simple and best practice solution for 4(ax+3)-ax=25+3a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(ax+3)-ax=25+3a equation:


Simplifying
4(ax + 3) + -1ax = 25 + 3a

Reorder the terms:
4(3 + ax) + -1ax = 25 + 3a
(3 * 4 + ax * 4) + -1ax = 25 + 3a
(12 + 4ax) + -1ax = 25 + 3a

Combine like terms: 4ax + -1ax = 3ax
12 + 3ax = 25 + 3a

Solving
12 + 3ax = 25 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
12 + -3a + 3ax = 25 + 3a + -3a

Combine like terms: 3a + -3a = 0
12 + -3a + 3ax = 25 + 0
12 + -3a + 3ax = 25

Add '-12' to each side of the equation.
12 + -3a + -12 + 3ax = 25 + -12

Reorder the terms:
12 + -12 + -3a + 3ax = 25 + -12

Combine like terms: 12 + -12 = 0
0 + -3a + 3ax = 25 + -12
-3a + 3ax = 25 + -12

Combine like terms: 25 + -12 = 13
-3a + 3ax = 13

Reorder the terms:
-13 + -3a + 3ax = 13 + -13

Combine like terms: 13 + -13 = 0
-13 + -3a + 3ax = 0

The solution to this equation could not be determined.

See similar equations:

| (2x-2)+(x+1)-x-(x+1)=60 | | Y=2x^2+13x-24 | | x^(1/3)=-0.5 | | 2x+y+15x-y=3 | | 1.1=3y+11.6 | | 3x-1.5=2(3x+6) | | 7x+3x^2= | | 3x+2(3x+5)= | | 1.8=0.7u+0.1u | | a=3a-36 | | 3-3x=4x-4x | | 4n+3=3 | | 4t-41=3t-20 | | (x)(5/4)/2=100 | | 8u-52=3u-2 | | (x)(5/4)/2=10 | | 2s+50=5s-13 | | 3x/11-9/11=-3/11 | | -20=-8x+5(x-7) | | -5/6x15 | | 2x-1=-2x+31 | | x=6.5+0.5y | | 3-3i/4i | | 1502x=195-1x | | (2x)^3/4x^2 | | 5w+5=40 | | X=16/cos(64) | | 3(r-16)=9 | | 5x+90=200 | | (2x-2)+(x+1)-x-(x+1)=(2x-9)+(x+1)+(x+8)+x | | [3(7-5)]/2 | | 3(1/3)-1 |

Equations solver categories